Function Evaluation of Common and Proposed Friction Shock Absorbers for Open Box Wagon 12-7019 KRVZ - Potapenko, Olga; Gorbunov, Nikolay; Mogyla, Valentin; Shcherbina, Yuriy; Hauser, Vladimir (Manufacturing Technology Journal, 2019)
This paper deals with the research of common and the proposed wedge type shock absorbers for bogie used by 12-7019 KRVZ open box type cargo wagon. Results of elements stress-deformation state caused by static load analysis performed by computer simulation are presented. Diagram of elements displacements, spring group compression dependence on vertical load, equivalent stresses of suspension system elements, proportional load distribution diagram and diagram of energy absorption by friction damper were obtained. The influence of spring group construction to the cargo wagon dynamics when running at speeds up 10 to 200 km/h was investigated. Advisability of the proposed wedge type shock absorbers construction improvements was confirmed.
Keywords: Wedge-Type Shock Absorber Construction; Disc Spring; Suspension System Deflection; Energy Absorption by Friction Damper; Dynamic Parameters